Testicular cytology in azoospermia - Prasad, Usha; Prasad, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Male infertility is a common problem and needs a minimally invasive method to arrive at the appropriate diagnosis. Alternative to open testicular biopsy the fine needle aspiration cytology of the testis is being increasingly used as a minimally invasive method of evaluating testicular function. Aim of the study: To assess the diagnostic accuracy of fine needle aspiration cytology in determining the causes of azoospermia. To establish that FNAC is cost effective, safe, out-patient investigation with no complications. Methods: Thirty nine patients with azoospermia in the age group of 20-40 years were included in the study. All the cases were subjected for Doppler study to rule out varicocele. Cord block was achieved with 1% lignocaine and aspiration was done with 23 gauge 1.5 inch needle. Smears were made on albuminised slides and stained with Leishman stain. Forresta et al. scoring system was adopted to analyse the smears. In the same sitting testicular biopsy was taken, fixed in Bouin’s fluid, routinely processed and stained with H&E stain. Results: The commonest group with infertility were in the age group 21-30 years. The testicular size was normal in 87.17% of subjects and 12.82% had small testis. Out of 39 subjects with azoospermia 38.46% subjects had varicocele. Varicocele was commonly associated with duct obstruction. The commonest causes observed in cases with azoospermia were; hypospermatogenesis with maturation arrest (4/39,10.25%), duct obstruction (12/39,30.76%), maturation arrest (7/39,17.94%), testicular atrophy (10/39,25.64%) and sertoli cell only syndrome (2/39,5.12%). In the present study diagnostic accuracy was 89.18%. Conclusions: Fine needle aspiration cytology is as informative as biopsy and can be done as a routine procedure. It helps us in ruling out obstructive and non-obstructive causes for azoospermia. In cases where FNAC shows normal spermatogenesis with azoospermia, biopsy and Doppler study is indicated to rule out duct obstruction which can be corrected surgically. It is a simple and cost effective.